Perceptions of physical activity by older adults: A qualitative study - Jancey, Jonine; Clarke, Ann; Howat, Peter; Maycock, Bruce; Lee, Andy (Sage Publications, 2009)
Objective: To identify issues and perceptions concerning physical activity in older adults. Design Qualitative study. Setting: Perth, Western Australia. Methods: Sixteen adults aged 65 to 74 years were interviewed in their own homes using a semi-structured interview schedule. Data were analysed using a descriptive qualitative methodology.Results: Participants believed that physical activity provided health benefits and reflected positively on physical activity experiences when they were younger, with many expressing a desire to engage in less age-appropriate activities. The major barrier to physical activity was pain. Participants described both positive and negative examples related to society’s support of physical activity. Conclusions: A number of issues were raised. These included: the need for more specific information on the benefits of physical activity; the role of pain management in physical activity; the concept that involvement in physical activity in younger years leads to involvement when older; and the expressed desire of older people to engage in less age-appropriate physical activities.